Absence of Neuronal Autoantibodies in Neuropsychiatric Systemic Lupus Erythematosus. Issue 6 (6th October 2020) - Varley, James A.; Andersson, Magnus; Grant, Eleanor; Berretta, Antonio; Zandi, Michael S.; Bondet, Vincent; Duffy, Darragh; Hunt, David; Piehl, Fredrik; Waters, Patrick; Irani, Sarosh R.
Abstract : This study aimed to characterise both neuronal autoantibodies and levels of interferon α, two proposed causative agents in neuropsychiatric systemic lupus erythematosus (NPSLE). Cerebrospinal fluid (CSF) and plasma from 35 patients with systemic lupus erythematosus (SLE; 15 with NPSLE) showed no antibodies against natively expressed N‐methyl‐D‐aspartate receptors (NMDARs), or the surface of live hippocampal neurons. By comparison to controls (n = 104), patients with SLE had antibodies that bound to a peptide representing the extracellular domain of NMDARs ( p < 0.0001), however, binding was retained against both rearranged peptides and no peptide (r = 0.85 and r = 0.79, respectively, p < 0.0001). In summary, neuronal‐surface reactive antibodies were not detected in NPSLE. Further, while interferon α levels were higher in SLE ( p < 0.0001), they lacked specificity for NPSLE. Our findings mandate a search for novel biomarkers in this condition. ANN NEUROL 2020;88:1244–1250